Cybersastra: Kontributifkah untuk Meningkatkan Literasi Sastra di Tengah Budaya Digital? - Pujayantie, Lenie Nuraeni; Mulyati, Yeti; Sumiyadi, S.; Halimah, Halimah (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
The rapid development of digital culture, characterized by instant access to information, has fostered an